Challenge and opportunity for vector control strategies on key mosquito-borne diseases during the COVID-19 pandemic - Lu, Hong-Zheng; Sui, Yuan; Lobo, Neil F.; Fouque, Florence; Gao, Chen; Lu, Shenning; Lv, Shan; Deng, Sheng-Qun; Wang, Duo-Quan (Frontiers in Public Health, 2023)
Mosquito-borne diseases are major global health problems that threaten nearly half of the world's population. Conflicting resources and infrastructure required by the coronavirus disease 2019 (COVID-19) global pandemic have resulted in the vector control process being more demanding than ever. Although novel vector control paradigms may have been more applicable and efficacious in these challenging settings, there were virtually no reports of novel strategies being developed or implemented during COVID-19. Evidence shows that the COVID-19 pandemic has dramatically impacted the implementation of conventional mosquito vector measures. Varying degrees of disruptions in malaria control and insecticide-treated nets (ITNs) and indoor residual spray (IRS) distributions worldwide from 2020 to 2021 were reported. Control measures such as mosquito net distribution and community education were significantly reduced in sub-Saharan countries. The COVID-19 pandemic has provided an opportunity for innovative vector control technologies currently being developed.Releasing sterile or lethal gene-carrying male mosquitoes and novel biopesticides may have advantages that are not matched by traditional vector measures in the current context. Here, we review the effects of COVID-19 on current mosquito vector control measures from 2020 to 2021 and discuss the future direction of vector control, taking into account probable evolving conditions of the COVID-19 pandemic.